2012
DOI: 10.14295/rbho.v18i1.696
|View full text |Cite
|
Sign up to set email alerts
|

Germinação das sementes e análise citogenética em duas espécies de palmeiras

Abstract: Germination of the seeds and cytogenetic analysis in two species of palmsEuterpe edulis and Archontophoenix alexandrae are palm trees used for ornamentation purpose and palm heart extraction. Seed germination and VGI, mitotic and meiotic chromosome behavior and quantification of pollen were assessed. For each species in each location and in each substracts, 60 seeds were used. Mitotic chromosome analyses and identification of differential nucleoli were made in meristem zone of primary root. Giemsa 2% (m/v) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The number of chromosomes found for the Oenocarpus species was the same as that found for other species of the tribe Euterpeae ( Battistin et al 2012 ; Oliveira et al 2016 ). The constancy in the number of chromosomes among closely related species is quite common among groups of Arecaceae ( Röser 1994 , 1995 ; Dransfield et al 2008 ; Corrêa et al 2009 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The number of chromosomes found for the Oenocarpus species was the same as that found for other species of the tribe Euterpeae ( Battistin et al 2012 ; Oliveira et al 2016 ). The constancy in the number of chromosomes among closely related species is quite common among groups of Arecaceae ( Röser 1994 , 1995 ; Dransfield et al 2008 ; Corrêa et al 2009 ).…”
Section: Discussionsupporting
confidence: 79%
“…Other chromosome numbers have been reported for species of the subfamily Arecoideae , to which the genus Oenocarpus belongs. Castilho et al (2000) , Corrêa et al (2009) , Battistin et al (2012) , and Pereira et al (2017) found 2n = 32 chromosomes for Elaeis guineensis (Jacquin, 1763), five species of Butia (Beccari, 1916), Archontophoenix alexandrae ((F. Muell.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation